Access for everyone? Australia's 'streaming wars' and consumers with disabilities. Issue 6 (2nd November 2017) - Ellis, Katie; Kent, Mike; Locke, Kathryn; Clocherty, Ceridwen
Abstract: This article is concerned with the recent rise in popularity of video-on-demand services as a form of entertainment in Australia and its premise of offering freedom to watch whatever, whenever. The article investigates how the entry of video-on-demand services into the Australian television market has both enabled and disabled televisual content access, focusing on how people with disability access video-on-demand content and the hardware and software they use to do this. It discusses how a lack of accessibility features, reduced useability and cumulative barriers to accessibility has led to failure of these services to be inclusive of everyone.